2020
DOI: 10.3390/cells9020300
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Induced C5a/C5aR1 Axis Activation in Pulmonary CD11b+ cDCs Promotes Pulmonary Tolerance through Downregulation of CD40

Abstract: Activation of the C5/C5a/C5a receptor 1 (C5aR1) axis during allergen sensitization protects from maladaptive T cell activation. To explore the underlying regulatory mechanisms, we analyzed the impact of C5aR1 activation on pulmonary CD11b+ conventional dendritic cells (cDCs) in the context of house-dust-mite (HDM) exposure. BALB/c mice were intratracheally immunized with an HDM/ovalbumin (OVA) mixture. After 24 h, we detected two CD11b+ cDC populations that could be distinguished on the basis of C5aR1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Previously, we demonstrated that C5aR1 controls the production of cytokines and chemokines that are associated with resistance to T. gondii infection ( 43 46 ). Here, we focused on the impact of C5aR1 activation on IL-12 as the main driver of IFN-γ production from NK cells and the development of protective Th1 immunity ( 4 , 10 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that C5aR1 controls the production of cytokines and chemokines that are associated with resistance to T. gondii infection ( 43 46 ). Here, we focused on the impact of C5aR1 activation on IL-12 as the main driver of IFN-γ production from NK cells and the development of protective Th1 immunity ( 4 , 10 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Activated canonically by pathogen‐associated molecular patterns associated with allergens or non‐canonically by allergen‐ or cell‐derived proteases, C3 or C5 are cleaved into different potent inflammatory mediators. Of those, the anaphylatoxins C3a and C5a exert not only strong pro‐allergic effector functions through activation of innate effector cells such as neutrophils, eosinophils and MC but also control allergen sensitization at the interface between dendritic, B and T cells, at least in mice [2].…”
Section: Innate Immunity In Allergic Diseasesmentioning
confidence: 99%
“…Similar to C3a and in concert with C3a, C5a can drive a proinflammatory environment through its strong chemotactic properties on neutrophils, monocytes, eosinophils, basophils, mast cell, and dendritic cell (DC) and its potency to activate such cells to release ROS, lysosomal enzymes, and proinflammatory cytokines such as IL‐1β, TNF‐α, IL‐6, and chemokines of the CC and CXC families (Figure 2). C5a also drives the activation and differentiation of T cells through DC maturation downstream of C5aR1 (Antoniou et al, 2020; Weaver et al, 2010). Also, C5a controls histamine‐induced increase in vasopermeability (Kordowski et al, 2019) and drives the production of metabolites of the arachidonic acid lipoxygenase and COX pathways resulting in increased production of LTB 4 or PGE 2 , both of which increase microvascular permeability (Karasu, Nilsson, Köhl, Lambris, & Huber‐Lang, 2019; Klos et al, 2009).…”
Section: Complement Therapy In Covid‐19 Patientsmentioning
confidence: 99%